CURBING ACTINOMYCETES AND THIDIAZURON ENHANCED MICROPROPAGATION IN THE RARE ALPINIA GALANGA - A MEDICINAL ZINGIBER - Rg, Baradwaj; Mv, Rao; T, Senthil Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Elimination of endophytic actinomycetes before micropropagation using antibiotic pre-treatment in rhizome bud explants of Alpinia galanga. Then, the formulation of an operative protocol for Micropropagation of the same void of endophytic actinomycetes. Methods: A treatment of mercury chloride and carbendazim, alone and in combination was used as surface sterilants. A pre-treatment of rifampicin and fusidic acid was used against actinomycete endophyte disinfection of rhizome bud explants. Then, Murashige and Skoog (MS) medium supplemented with various concentrations of cytokinins were used for micropropagation of disinfected explants. Results: A treatment of 0.1% (w/v) mercury chloride and 0.1% (w/v) carbendazim, one after the other for 5 minutes gave the best sterility of 83.3%. A pre-treatment of Rifampicin 100 mg/l and fusidic acid 100 mg/l for 2 hrs gave the best disinfection of 70% against actinomycete endophytes. A combination of thidiazuron (TDZ) 0.45 Î¼M and 6-benzyladenine 13.32 Î¼M in MS medium resulted in 9.4 shoots per explant. MS medium fortified with 10.74 Î¼Mof 1-naphthaleneacetic acid gave the best rooting of 20 roots/shoot. inter simple sequence repeat marker genetic similarity of regenerants with the mother plant was confirmed. Conclusion: This study shows the potency of Rifampicin and Fusidic acid to disinfect explants from actinomycete endophytes and is significant as the first report on curbing actinomycetes endophytes in plant tissue culture of A. galanga. This is also the first report conferring the dissimilar regeneration capabilities of TDZ in comparison to other cytokinins in Zingiberaceae.